Evaluation of Religious Development of Junior High School Students Hikmah Teladan Based on the Religious Dimension in Forming Religious Independence - Fitriani, Fitriani; Basri, Hasan; Suhartini, Andewi; Amin, Azizah Amini binti (EDUKASIA, 2024)
This research aims to discuss the evaluation of the religious development of students at SMP Hikmah Teladan based on religious dimensions in fostering independence in worship. This study uses a qualitative approach, a field research type, and employs a descriptive method, using the descriptive analysis model by Miles and Huberman (Qualitative Data Analysis), which includes data reduction, data presentation, and conclusion drawing. Data collection techniques include interviews, observation, and documentation. The results of this study indicate that the religious development of students at SMP Hikmah Teladan in fostering independence in worship must continue to be pursued by referring to religious dimensions. The novelties in this research include: 1) categorizing religious programs based on religious dimensions; 2) conducting evaluations systematically; 3) measuring target achievement using independence indicators, so that progress can be more measurable. Therefore, the religious development program for students at SMP Hikmah Teladan supports the formation of independence in worship.